Experimental infectious bursal disease in the ostrich (Struthio camelus) - Mendes, A. R.; Luvizotto, Maria Cecília Rui [UNESP]; Ferrari, H. E.; Neto, M. G.; Cardoso, T. C. (Elsevier B.V., 2007)
Clinically severe disease was produced in ostriches aged 4 weeks by oral infection with avirulent strain of infectious bursal disease virus (vIBDV), namely strain Faragher 52/70. Four days after infection the birds were humanely killed and tissue samples, including thymus, bursa of Fabricius (BF), brain and kidney were collected for examination. Histopathologically, the thymus and BF showed severe lymphoid depletion and necrosis, while immunolabelling with a polyclonal antibody demonstrated abundant viral antigen. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: infectious bursal disease; ostrich; Struthio camelus; viral infection